Nitrous oxide and nitric oxide emissions from lowland rice cultivation with urea deep placement and alternate wetting and drying irrigation - Islam, S. M. Mofijul; Gaihre, Yam Kanta; Biswas, Jatish Chandra; Singh, Upendra; Ahmed, Md. Nayeem; Sanabria, Joaquin; Saleque, M.A. (Springer, 2018)
Urea deep placement (UDP) and the alternate wetting and drying (AWD) irrigation method are two promising rice production technologies. However, studies on the impact of UDP under AWD irrigation on nitrous oxide (N2O) and nitric oxide (NO) emissions are limited. In this study, the effects of UDP with AWD irrigation on these emissions, nitrogen use efficiency (NUE), and rice yields are investigated, compared to conventional broadcast application. N2O and NO emissions from three fertilizer treatments – no nitrogen, UDP, and broadcast application of prilled urea (PU) – were measured. Measurements were taken using an automated gas sampling and analysis system continuously for two consecutive Boro (dry) rice seasons. N2O emission peaks were observed after broadcast application of PU but not after UDP. In contrast, large spikes in N2O emission were observed after UDP, compared to broadcast application, during dry periods. Despite differences in emission peaks, seasonal cumulative N2O emissions from UDP and broadcast treatments were similar. However, NO emissions were minimal and unaffected by UDP or AWD. UDP increased rice yields by 28% and N recovery efficiency by 167%, compared to broadcast urea. This study demonstrates that UDP with AWD irrigation can increase yields and NUE without increasing N2O and NO emissions.